Utilization of Plastic Bag Waste Into Polybags as a Growing Media in West Bungus - Bulkia Rahim; Ulfi Anggraini; Intan Zulian Apri; Lusi Vidia Putri; Malika Afifah Keysha; Putri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The people of RW 03, Bungus Barat Subdistrict, Bungus Teluk Kabung District, have not yet optimized the utilization of waste, especially plastic waste. The use of plastic waste as a planting medium is an effective way to increase public awareness about the importance of managing plastic waste. This activity is also a means of learning and motivating the community to be able to utilize waste plastic bags and plastic bottles as planting media. The research method used is descriptive qualitative with direct observation data collection techniques and direct interviews with informants. Observations were carried out by Padang State University Real Work Lecture Students. This activity took place at MTsN 7 Padang with the observation instrument of OSIM members and administrators, as well as socializing the importance of managing plastic waste and how to process plastic waste into something useful such as polybags.